2020
DOI: 10.3389/fnins.2020.00681
|View full text |Cite
|
Sign up to set email alerts
|

Toward Long-Term Communication With the Brain in the Blind by Intracortical Stimulation: Challenges and Future Prospects

Abstract: The restoration of a useful visual sense in a profoundly blind person by direct electrical stimulation of the visual cortex has been a subject of study for many years. However, the field of cortically based sight restoration has made few advances in the last few decades, and many problems remain. In this context, the scientific and technological problems associated with safe and effective communication with the brain are very complex, and there are still many unresolved issues delaying its development. In this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 86 publications
(106 reference statements)
0
26
0
2
Order By: Relevance
“…Therefore, the perceptions induced by intracortical microstimulation appear to be more complex than initially believed and the generation of arbitrary patterns or recognizable letters is not a simple matter. Consequently, a key challenge for the future development of cortical visual implants is the delivery of interpretable information to the brain (9). In addition, most current coding strategies are only aimed at addressing spatial details, but we should also pay attention to other relevant visual attributes such as receptive field size, orientation and movement.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the perceptions induced by intracortical microstimulation appear to be more complex than initially believed and the generation of arbitrary patterns or recognizable letters is not a simple matter. Consequently, a key challenge for the future development of cortical visual implants is the delivery of interpretable information to the brain (9). In addition, most current coding strategies are only aimed at addressing spatial details, but we should also pay attention to other relevant visual attributes such as receptive field size, orientation and movement.…”
Section: Discussionmentioning
confidence: 99%
“…To circumvent these limitations, Beauchamp et al developed two innovations: current steering procedures and rapid sequential stimulation of electrodes to produce a sequence of phosphenes that traces out the shape of the intended pattern. However, although current steering and sequential stimulation can help to improve the utility of a cortical visual prosthesis with surface electrodes, there are still a number of challenges to overcome (8,9). For example, every pulse train on a given electrode had to be completed before a pulse train on a second electrode could begin.…”
Section: Introductionmentioning
confidence: 99%
“…Fernandez and colleagues recently implanted the UEA in the occipital cortex of a 57-year-old person during a six-month period. They found that stimulation thresholds necessary to induce phosphenes were in the 1-100 µA range [35]. This threshold also depends on the depth of stimulation as reported by De Yoe and colleagues in monkeys [27].…”
Section: Visual Cortical Prosthesis and Intracortical Electrodesmentioning
confidence: 75%
“…For many cases of blindness, there currently exists no effective treatment. However, neuroprosthetic implants are a promising technology for restoring some form of vision via electrical neurostimulation in the visual pathway ( Chen, Wang, Fernandez, & Roelfsema, 2020 ; Fernández, Alfaro, & González-López, 2020 ; Lewis et al, 2016 ; Lewis, Ackland, Lowery, & Rosenfeld, 2015 ; Riazi-Esfahani et al, 2014 ; Roelfsema, Denys, & Klink, 2018 ; Shepherd et al, 2013 ; Tehovnik & Slocum, 2013 ; Tehovnik, Slocum, Smirnakis, & Tolias, 2009 ; Pezaris & Reid, 2007 ). Using multiple electrodes, such implants can activate a specific arrangement of visual neurons based on camera input.…”
Section: Introductionmentioning
confidence: 99%
“…The greater the number of implanted electrodes, the more phosphenes can be elicited. In this study, we focus on cortical implants that, compared with other types of implants, such as retinal implants, are expected to have a wider range of therapeutic applicability ( Fernández, Alfaro, & González-López, 2020 ), are less amenable to electrical crosstalk ( Davis et al, 2012 ; Wilke et al, 2011 ), and can accommodate a larger number of electrodes. For instance, recently, Chen, Wang, Fernandez, and Roelfsema (2020) successfully implanted more than one thousand cortical electrodes to achieve artificial visual perception in macaque monkeys.…”
Section: Introductionmentioning
confidence: 99%